Relationship between Prolactin Plasma Levels and White Matter Volume in Women with Multiple Sclerosis. (8th July 2015) - De Giglio, L.; Marinelli, F.; Prosperini, L.; Contessa, G. M.; Gurreri, F.; Piattella, M. C.; De Angelis, F.; Barletta, V. T.; Tomassini, V.; Pantano, P.; Pozzilli, C.
Abstract : Background . The role of prolactin (PRL) on tissue injury and repair mechanisms in multiple sclerosis (MS) remains unclear. The aim of this work was to investigate the relationship between PRL plasma levels and brain damage as measured by magnetic resonance imaging (MRI). Methods . We employed a chemiluminescence immunoassay for measuring plasma levels of PRL. We used a 1.5 T scanner to acquire images and Jim 4.0 and SIENAX software to analyse them. Results . We included 106 women with relapsing remitting (RR) MS and stable disease in the last two months. There was no difference in PRL plasma levels between patients with and without gadolinium enhancement on MRI. PRL plasma levels correlated with white matter volume (WMV) (rho = 0.284, p = 0.014 ) but not with grey matter volume (GMV). Moreover, PRL levels predicted changes in WMV (Beta: 984, p = 0.034 ). Conclusions . Our data of a positive association between PRL serum levels and WMV support the role of PRL in promoting myelin repair as documented in animal models of demyelination. The lack of an increase of PRL in the presence of gadolinium enhancement, contrasts with the view considering this hormone as an immune-stimulating and detrimental factor in the inflammatory process associated with MS.